The impact of electronic audit in raising of the independence and professional efficiency of the internal auditor - برزان صبيحة (Journal of Economics and Administrative Sciences, 2018)
The research aims to shed light on the role of E-Audit in raising Independence and professional competence of the external auditor, the study has been applied on a sample of the branches of the Rafidain Bank n have been addressed research topic beside the theoretical, as put forward by the literature of accounting, audit and that the contents of the section first, either the practical side was required to test the hypotheses use form questionnaire, which was distributed to a sample of the external auditors and bankers research sample. He has applied for his part in the search for a standard of independence and professionalism of the external auditor and the factors influencing these standards, and the most important findings of the research: - 1.E-Audit leads to the separation of audit work and the work of the committees assigned to the auditor within the units. 2. The first task of the auditor in all units is to examine the internal control system in units of the research sample, therefore, the presence of electronic information system sound for the activities of the units sample leads to the ease and efficiency of the examination of the internal control system and thus the discovery of errors less time, effort and cost. 3. Leads to disallow electronic information system for people who are not licensed or authorized to enter and thus does not give the opportunity for manipulation of information and the results of the audit units in the research sample. 4. Leads checking mail checker to make more efficient and work experience in the field of computer data processing electronically and thus enable him to perform the procedures adopted by the sample units in the audit process